From Uterus to Brain: An Update on Epidemiology, Clinical Features, and Treatment of Brain Metastases From Gestational Trophoblastic Neoplasia - Borella, Fulvio; Cosma, Stefano; Ferraioli, Domenico; Preti, Mario; Gallio, Niccolò; Valabrega, Giorgio; Scotto, Giulia; Rolfo, Alessandro; Castellano, Isabella; Cassoni, Paola; Bertero, Luca; Benedetto, Chiara (Frontiers in Oncology, 2022)
In this review, we provide the state of the art about brain metastases (BMs) from gestational trophoblastic neoplasia (GTN), a rare condition. Data concerning the epidemiology, clinical presentation, innovations in therapeutic modalities and outcomes of GTN BMs are comprehensively presented with particular attention to the role of radiotherapy, neurosurgery and the most recent chemotherapy regimens. Good response rates have been achieved thanks to multi-agent chemotherapy, but brain involvement by GTNs entails significant risks for patients’ health since sudden and extensive intracranial hemorrhages are possible. Moreover, despite the evolution of treatment protocols, a small proportion of these patients ultimately develops a resistant disease. To tackle this unmet clinical need, immunotherapy has been recently proposed. The role of this novel option for this subset of patients as well as the achieved results so far are also discussed.